2021
DOI: 10.3390/polym13101582
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Polyhydroxyalkanoates Granules in Haloferax mediterranei by Double-Fluorescence Staining with Nile Red and SYBR Green by Confocal Fluorescence Microscopy

Abstract: Haloferaxmediterranei is a haloarchaeon of high interest in biotechnology because it produces and mobilizes intracellular polyhydroxyalkanoate (PHA) granules during growth under stress conditions (limitation of phosphorous in the culture media), among other interesting metabolites (enzymes, carotenoids, etc.). The capability of PHA production by microbes can be monitored with the use of staining-based methods. However, the staining of haloarchaea cells is a challenging task; firstly, due to the high ionic stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Hfx. mediterranei has proved to be useful in the production of bioplastics like polyhydroxyalkanoates (PHA) [30][31][32][33] and is considered a model microorganism in a variety of fields, including the nitrogen cycle [28,34].…”
Section: Introductionmentioning
confidence: 99%
“…Hfx. mediterranei has proved to be useful in the production of bioplastics like polyhydroxyalkanoates (PHA) [30][31][32][33] and is considered a model microorganism in a variety of fields, including the nitrogen cycle [28,34].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them accumulate PHAs in their cytoplasm as granules at a high productivity rate. The cells produce and accumulate PHAs within the cells as a subcellular energy source and these biopolymers are usually produced when the microorganisms showing this metabolic capability are cultured with nutrient-limiting concentrations of nitrogen, phosphorus, sulphur, or oxygen and excess carbon sources (Cánovas et al, 2021;Simó-Cabrera et al, 2021). The most produced PHAs by microbes are polyhydroxybutyrate (PHB) although the most marketed is PHBV due to its physicochemical characteristics.…”
Section: Biological Synthesis Of Phasmentioning
confidence: 99%
“…PHAs, discovered by Lemoigne in 1925 inside Bacillus megaterium cells (Doudoroff and Stanier, 1959), are linear polyesters of (R)-hydroxyl fatty acid monomers (Tan et al, 2014b;Kumar et al, 2017). They accumulated in the cytoplasm of various microorganisms in the form of granules, serving as a source of energy and carbon, particularly in the presence of excess carbon and limited essential nutrients such as nitrogen, phosphorus, or oxygen (Cánovas et al, 2021;Koller et al, 2007;Kumar et al, 2017;Obruca et al, 2018;Rivera-Briso and Serrano-Aroca, 2018). It is documented that granules are composed of 97.5% PHA, 2% proteins (PHA synthases, PHA depolymerases, phasins, and regulatory proteins) and 0.5% lipids (Cai et al, 2012;Cai et al, 2015;Amabile et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…The gas vesicles mentioned in section "1. Introduction: haloarchaeal diversity and ecology" have applications in drug delivery systems and vaccine development (Cánovas et al, 2021). Meanwhile, poly-β-hydroxy-alkanoates (PHAs) produced by haloarchaea, such as Haloferax mediterranei, are considered an alternative to plastics produced from petroleum and in medical applications owing to their biocompatibility (Salgaonkar et al, 2013;Li et al, 2021).…”
Section: Biotechnological Significance Of Haloarchaeamentioning
confidence: 99%
“…A recent study showed a ∼165% increase in the output of PHA when citZ and gltA genes were downregulated by CRISPRi (Lin et al, 2021). Recently, robust methods have been developed for monitoring PHA granules in Haloferax mediterranei, such as through confocal 10.3389/fmicb.2023.1113540 fluorescence microscopy stained with Nile red and SYBR Green (Cánovas et al, 2021).…”
Section: Biodegradable and Biocompatible Polymers By Haloarchaeamentioning
confidence: 99%